A composite cathode material encapsulated by amorphous garnet-type solid electrolyte and self-assembled La2(Ni0.5Li0.5)O4 nanoparticles for all-solid-state batteries. Issue 43 (30th October 2020) - Heo, Kookjin; Lee, Jonggwan; Im, Jehong; Kim, Min-Young; Kim, Ho-Sung; Ahn, Docheon; Kim, Jaekook; Lim, Jinsub
Abstract : In this article, we report the effect of surface modification of NCM80 [Li(Ni0.8 Co0.1 Mn0.1 )O2 ] cathode materials on the performance of all-solid-state batteries (ASSBs) with oxide-based organic/inorganic hybrid solid electrolytes. Abstract : In this article, we report the effect of surface modification of NCM80 [Li(Ni0.8 Co0.1 Mn0.1 )O2 ] cathode materials on the performance of all-solid-state batteries (ASSBs) with oxide-based organic/inorganic hybrid solid electrolytes. A Ni-Rich cathode material Li(Ni x Co(1− x )//2 Mn(1− x )/2 )O2 ( x > 0.6) (NCM) with high specific capacity and a layered structure is a suitable cathode material for next-generation energy storage systems such as ASSBs, particularly for electric vehicles and portable devices. However, for ASSBs, resistance at the interface between the cathode and solid electrolyte is larger than that of the liquid electrolyte because of point contact. To solve this problem, we fabricated a composite cathode material encapsulated by amorphous garnet-type solid electrolyte and La2 (Ni0.5 Li0.5 )O4 nanoparticles. Therefore, the structure, cycling stability, and rate performance of the composite-NCM80 cathode material in ASSBs with oxide-based organic/inorganic hybrid electrolytes were investigated using powder X-ray diffraction analysis, field-emission scanning electron microscopy, electrochemical impedance spectroscopy, and galvanostatic measurements.